TEAMWORK COMMUNICATION STRATEGIES IN ENHANCING TQM IMPLEMENTATION IN MANUFACTURING ORGANIZATIONS IN MALAYSIA - Sharina Samsudin; Che Azlan Taib; Fadzli Shah Abd Aziz, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The term teamwork is so popular in organizations and had always been a way to do work in order to increase productivity. In fact, organizations use this word to motivate employees through posters hanging on office walls and to empower employees to a certain extent. However, although teamwork is often easy to observe, but the practice and strategies of communication used in building and maintaining teamwork are always difficult to describe and yet more difficult to produce. In this article, we present teamwork communication strategies in TQM implementation in Malaysia manufacturing organizations. This study was done using qualitative in-depth interview. The study had been carried out in five manufacturing organizations originating from three different continents; two Malaysian local organizations, two eastern and one western organization, and all of them located in Malaysia. In selecting the informants, the study adopts a judgment type of purposive sampling techniques. Results show that the most preferable strategies of communication for teamwork are tell and sell, identify and reply, and underscore and explore. Whereas the formal internal-operational communication, besides informal and personal communication are the preferred practice of communication at a certain level. A reliable medium of communication for teamwork is still face-to-face meetings.